Discontinuation of Breast Feeding in Infants - Muhammad Akram Saeed, Samina Badar, Seema Yasmeen, Wajahat Hussain (Journal of Rawalpindi Medical College, 2013)
Background: To determine self-reported reasons for discontinuation of breastfeeding (BF) of infants by mothers. Methods: In this cross sectional descriptive study ,mothers having a child less than 12 months of age were slected by non-probability convenient sampling techniquue. Data was collected by using pretested close ended questionnaire by the researchers. In addition to universal variables, descriptive analysis of the reasons of discontinuation of BF was done. Pearson coefficient correlation test was applied to know the relationship between socioeconomic variables and discontinuation of breastfeeding. Results:Among the respondents 54% discontinued breastfeeding before 6 months and out of that 50% discontinued between the first 2-3 months.Most common reasons found for discontinuation of breastfeeding were insufficient milk production (52%), conception (19%) and child sickness (12%).Higher education, as years of schooling, decreases the discontinuation rate of breastfeeding (r=0.27) whereas the duration of breastfeeding has inverse relationship with per day working hours for wages of the mothers (r= -0.67) and their income level (r= -0.67). Conclusion: Awareness regarding the benefits of breastfeeding must be highlighted